EFFECT OF METHOD OF PLANTING OF IN VITRO PLANTLETS ON POTATO MINI-TUBER PRODUCTION UNDER PROTECTED CONDITIONS - buckseth, tanuja (Potato Journal, 2018)
High production cost has always been an impediment to the adoption of tissue culture techniques, and it has further limited the technology to a few institutions and rich farmers while locking out the resource-challenged subsistence farmers. In order to increase application of tissue culture technology in potato farming, innovative approaches are needed to lower the cost of seed potato production. Keeping in view the fact that presently no information is available on the subject, an attempt has been made to explore the possibility of reducing the costs on plantlets as well as for rapid multiplication of precious planting material by using the micro- plantlets in different ways mainly after cutting in upper and lower half in potato variety Kufri Himalini. From the study it was concluded that for the effective utilization of precious planting material, use of in vitro plantlets after cutting in two halves is a viable option for the production of mini-tubers. It will nearly double the number and yield of mini-tubers/m2, over the one got from full plantlets.